1992
DOI: 10.1038/ki.1992.344
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated MHC-class II expression and γ-IFN and soluble IL-2R in lupus nephritis

Abstract: Expression of MHC-class II molecules (HLA-DR and -DQ), serum gamma-interferon (gamma-IFN) and soluble interleukin-2 receptor (sIL-2R) levels were studied in 35 Japanese patients with lupus nephritis (LN) to clarify intraglomerular cellular activation and cytokine involvement in human LN. In 11 normal kidney specimens, HLA-DR(Ia1) was noted in glomerular tufts, but HLA-DQ was either not or was faintly detected in glomeruli by the indirect immunofluorescence technique. HLA-DR and -DQ were observed mainly on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 23 publications
1
28
0
1
Order By: Relevance
“…Glomerular MHC-II expression is increased in lupus patients, and this increase correlated with disease activity, whereas prednisolone therapy reduced MHC-II expression (10), suggesting that targeting glomerular MHC-II expression may be a useful approach in lupus patients. There are a number of other possible mechanisms by which atorvastatin might reduce glomerular injury, including a reduction in cellular proliferation via modulation of the Rho GTPase signaling pathway (23) and a reduction in trafficking of macrophages and lymphocytes to the glomerulus (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…Glomerular MHC-II expression is increased in lupus patients, and this increase correlated with disease activity, whereas prednisolone therapy reduced MHC-II expression (10), suggesting that targeting glomerular MHC-II expression may be a useful approach in lupus patients. There are a number of other possible mechanisms by which atorvastatin might reduce glomerular injury, including a reduction in cellular proliferation via modulation of the Rho GTPase signaling pathway (23) and a reduction in trafficking of macrophages and lymphocytes to the glomerulus (4,24).…”
Section: Discussionmentioning
confidence: 99%
“…13 IFN-γ or molecules that are upregulated by IFN-γ, such as IFN-γ-inducible protein 10 (CXCL-10), human leukocyte antigen (HLA) class II and neopterin, are present at increased levels in patients with SLE, including those with LN, and have been associated with disease activity and flares. [14][15][16][17][18][19][20] AMG 811 is a fully human (IgG1) anti-IFN-γ antibody. In patients with mild-to-moderate SLE, single doses of AMG 811 normalised IFN-regulated gene expression, led to dose-related reductions in serum CXCL-10, and were well tolerated.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that MHC class II antigen expression is enhanced in lupus nephritis in humans and in mice models. [5][6][7] Therefore a particular allele of the polymorphic gene which plays a part in the regulation of MHC class II expression might be involved in the predisposition to SLE. In this report, we examine the association between SNPs in the human CIITA gene, MHC2TA, and SLE.…”
mentioning
confidence: 99%